ISSUES OF COMBATING IDEOLOGICAL SECURITY THREATS - Salaeva Laylo Shavkatovna (The Conference Hub, 2025)
In the modern world, the intensification of globalization, information warfare, and digital transformation has made ideological security a pressing geopolitical issue. Hybrid conflicts, manipulation based on artificial intelligence, and ideological pressures through mass culture are being used as strategic tools to weaken national consciousness. For this reason, the issue of ideological security is increasingly being reinterpreted not as a military-political defense, but as a means of controlling social consciousness.